2019
DOI: 10.1002/ep.13275
|View full text |Cite
|
Sign up to set email alerts
|

Suitable business models for innovation in different levels of the smart grid energy industry

Abstract: An intelligent grid system makes the combination of various renewable energy technologies and changes in power supply and demand become more possible. Technology and innovation are considered the primary drivers of the next stage of economic growth in China, and smart grid (SG) energy management has developed as an emerging industry with the goal of lowering greenhouse gas emissions and increasing energy efficiency to attain sustainability. In this study, high‐level, middle‐level, and low‐level managers from 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Costa-Campi et al (2014) used a structural model to explore new energy Spanish companies and found that the higher the R&D intensity, the more it promoted the new energy industry. Data research on new energy manufacturing companies in China found that technology diversification and R&D cooperation helped new energy production companies to reduce production costs and promote rapid industrial growth (Yun et al, 2019;Chen et al, 2020). However, some literature found that the relationship between technological progress and the new energy industry was not linear, but a positive U-shaped nonlinear relationship (Xu and Lin, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Costa-Campi et al (2014) used a structural model to explore new energy Spanish companies and found that the higher the R&D intensity, the more it promoted the new energy industry. Data research on new energy manufacturing companies in China found that technology diversification and R&D cooperation helped new energy production companies to reduce production costs and promote rapid industrial growth (Yun et al, 2019;Chen et al, 2020). However, some literature found that the relationship between technological progress and the new energy industry was not linear, but a positive U-shaped nonlinear relationship (Xu and Lin, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Their study confirms the prediction that IT exploration positively affects NCBM. According to Chen et al . (2019), by creating new activities or new relationships with external actors, NCBM facilitates the use of current technologies.…”
Section: Framework and Hypotheses Developmentmentioning
confidence: 99%
“…In the Schumpeterian growth theory, research and innovation are market conducts for entrepreneurs pursuing maximum profits. A company's R&D input directly affects its independent innovative capabilities, which makes it difficult for its products to be copied or replaced [14,15]. Therefore, research and innovation are the core for the company to improve its performance and eventually surpass its competitors [16][17][18].…”
Section: Relationships Between Randd Intensity and Firms' Performancementioning
confidence: 99%